Boris Purvi . Boris the First - Sharaliev, Borislav (SIF Boyana, 1984)
Duration: 02:28:00 Prince Boris the First ruled Bulgaria in the late 9th century: the film is a hagiographic account of his life. In his youth, he suffered military defeats, but succeeded in keeping the territorial integrity of the country by seeking peace with the Slavic neighbors. During his reign, Bulgaria breaks with paganism and joins the Christian community, albeit paying a heavy death toll. When one of his sons wants to return to paganism, Boris condemns and blinds him. Having unified and Christianized the country, as well as having secured a Cyrillic alphabet for the nation, Boris retires to a monastery and is later included in the pantheon of Bulgarian saints.